Strategic incentives to human capital - Gambardella, Alfonso; Panico, Claudio; Valentini, Giovanni (Strategic Management Journal, 2015)
Motivating human capital in knowledge‐intensive activities is a serious managerial challenge because it is difficult to link rewards to actions or performance. Firms instead might motivate knowledge workers by offering them opportunities to increase personal benefits (e.g., learning, satisfaction) through autonomy in the decision‐making process. Our model shows that firms can offer less autonomy in projects closer to their core business: Because firm specialization raises the value of the project's outcomes, it also increases the benefits for knowledge workers, who derive motivation even though they make fewer decisions to support their realization of personal goals. Projects farther from the core offer weaker firm contributions, so firms can motivate knowledge workers by allowing them to benefit from greater autonomy. We discuss several implications of our analysis . Copyright © 2013 John Wiley & Sons, Ltd.